Kajian Literatur atas Dinamika Isu Privasi Data dan Kepercayaan pada pengguna E-Commerce di Indonesia - Hotni Pinta Laura Hutabarat; Jonathan Edgarian; Catharina Aprilia Hellyani (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
This literature review analyzes the impact of data privacy issues on consumer usage intention in Indonesian e-commerce platforms. The study aims to map privacy threats and understand the phenomenon of the privacy paradox in the context of digital retail. Using a literature review method, this study synthesized findings from international journals published in the last five years from Scopus, Web of Science, and Google Scholar databases. The results show that excessive data collection, unauthorized secondary use, and data breaches significantly increase consumer privacy concerns. However, the research also confirms a privacy paradox, where consumers willingly share personal data to gain shopping convenience and promotions. The findings highlight that strong brand trust and a seamless user experience can effectively mitigate these privacy fears. Practically, this study recommends that e-commerce companies implement the Privacy by Design framework, utilize dynamic passwords (OTP), and provide transparent privacy settings as a competitive marketing advantage. Future research should explore specific regional demographics and the direct impact of new technologies like AI chatbots on consumer security perceptions.